Influence of serum levels of vitamin D on IgE response in schoolchildren with asthma in poor communities - Eduardo Egea; Gloria Garavito; Luis Carlos Fang-Mercado; Dary Luz Mendoza; José Miguel Escamilla; Elsie De los Rios; Rodolfo Dennis; Mario Sanchez-Borges (Revista Alergia México, 2016)
Background: Asthma is a common disease in the world and vitamin D (Vit-D) has been associated with the presence and severity of this disease.